A magnetic resonance imaging-based prognostic scoring system to predict outcome in transplant-eligible patients with multiple myeloma - Mai, Elias K.; Kloth, Jost; Merz, Maximilian; Shah, Sofia; Raab, Marc-Steffen; Hillengaß, Michaela; Wagner, Barbara; Jauch, Anna; Hose, Dirk; Weber, Marc-André; Goldschmidt, Hartmut; Hillengaß, Jens (Haematologica, 2015)
Diffuse and focal bone marrow infiltration patterns detected by magnetic resonance imaging have been shown to be of prognostic significance in all stages of monoclonal plasma cell disorders and have, therefore, been incorporated into the definition of the disease. The aim of this retrospective analysis was to develop a rapidly evaluable prognostic scoring system, incorporating the most significant information acquired from magnetic resonance imaging. Therefore, the impact of bone marrow infiltration patterns on progression-free and overall survival in 161 transplant-eligible myeloma patients was evaluated. Compared to salt and pepper/minimal diffuse infiltration, moderate/severe diffuse infiltration had a negative prognostic impact on both progression-free survival (P<0.001) and overall survival (P=0.003). More than 25 focal lesions on whole-body magnetic resonance imaging or more than seven on axial magnetic resonance imaging were associated with an adverse prognosis (progression-free survival: P=0.001/0.003 and overall survival: P=0.04/0.02). A magnetic resonance imaging-based prognostic scoring system, combining grouped diffuse and focal infiltration patterns, was formulated and is applicable to whole-body as well as axial magnetic resonance imaging. The score identified high-risk patients with median progression-free and overall survival of 23.4 and 55.9 months, respectively (whole-body-based). Multivariate analyses demonstrated that the magnetic resonance imaging-based prognostic score stage III (high-risk) and adverse cytogenetics are independent prognostic factors for both progression-free and overall survival (whole-body-based, progression-free survival: hazard ratio=3.65, P<0.001; overall survival: hazard ratio=5.19, P=0.005). In conclusion, we suggest a magnetic resonance imaging-based prognostic scoring system which is a robust, easy to assess and interpret parameter summarizing significant magnetic resonance imaging findings in transplant-eligible patients with multiple myeloma.
Gesehen am 25.04.2017